2006
DOI: 10.1186/1476-069x-5-29
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of mercury exposure and blood pressure in the Brazilian Amazon

Abstract: Background: Fish is considered protective for coronary heart disease (CHD), but mercury (Hg) intake from fish may counterbalance beneficial effects. Although neurotoxic effects of methylmercury (MeHg) are well established, cardiovascular effects are still debated. The objective of the present study was to evaluate blood pressure in relation to Hg exposure and fish consumption among a non-indigenous fish-eating population in the Brazilian Amazon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
2
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(148 citation statements)
references
References 62 publications
7
128
2
11
Order By: Relevance
“…In these populations, there is strong evidence of early nervous system dysfunction and, to a less extent, immunologic and cardiovascular effects among both adults and children (Lebel et al, 1996(Lebel et al, , 1998Grandjean et al, 1999;Amorim et al, 2000;Dolbec et al, 2000;Harada et al, 2001;Cordier et al, 2002;Mergler, 2002;Yokoo et al, 2003;Silbergeld et al, 2005;Fillion et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In these populations, there is strong evidence of early nervous system dysfunction and, to a less extent, immunologic and cardiovascular effects among both adults and children (Lebel et al, 1996(Lebel et al, , 1998Grandjean et al, 1999;Amorim et al, 2000;Dolbec et al, 2000;Harada et al, 2001;Cordier et al, 2002;Mergler, 2002;Yokoo et al, 2003;Silbergeld et al, 2005;Fillion et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that higher hair mercury content is associated with increased risk of CVD in men in this study population. 19,31 Other studies have found a positive association between mercury exposure and blood pressure not only in populations with high mercury exposure, [20][21][22][23] but also among non-fish consumers. 37 However, our Long-chain n-3 PUFA, mercury and blood pressure JK Virtanen et al results indicate that a moderate mercury exposure is not associated with blood pressure, and also the overall evidence regarding the association between mercury exposure and blood pressure is considered weak.…”
Section: Discussionmentioning
confidence: 98%
“…19 Mercury has also been associated with blood pressure in other, but mainly highly exposed study populations. [20][21][22][23] However, little is known about the relationship in populations with low to moderate exposure levels.…”
Section: Introductionmentioning
confidence: 99%
“…Megler e colaboradores publicaram em 2007 uma revisão sobre efeitos na saúde da exposição ao mercúrio e, além dos efeitos que já mencionamos anteriormente, também citam uma possível associação com efeitos cardiovasculares, como infarto do miocárdio agudo, doença isquêmica do coração, efeitos sobre pressão sanguínea e hipertensão, embora se reconheça que a associação é fraca, e atualmente esses efeitos ainda não sejam completamente entendidos, porque têm sido reportados resultados contraditórios nos diversos estudos sobre esse tema em adultos (Salonen et al, 1995;Salonen et al, 2000;Stern, 2005;Vupputuri et al, 2005;Fillion et al, 2006;Virtanen et al, 2007;Mozaffarian, 2009) e é um efeito não tem sido estudado em criança.…”
Section: Efeitos Do Mercúrio Na Saúdeunclassified